A incidência do PIS e da COFINS sobre as receitas das operações de crédito - Andrade, Leonardo Augusto (2023)
Brazilian Tax Law has deep roots in the Federal Constitution, from which it draws its legitimacy and organization. The achievement of the fundamental objectives of the Republic strongly depends on tax collection, especially considering that tax revenue generation is derived from the private sector’s activities. In this scenario, the fundamental duty of paying taxes arises, eliminating the necessity for the State to generate income streams independently. The execution of taxation, however, is legitimate as far as both formal and material limits provisioned by the Constitution are respected. The limitations to the execution of Taxation represents, in that sense, individual rights that integrate the irrevocable part of the Constitution, that cannot be changed even by Constitutional Amendments. Notwithstanding, the Constitution predicted that certain fundamental rights, such as “Legality” and “Anteriority”, need to make room for the execution of certain public policies related to specific economic sectors, establishing mitigations and exceptions to those rules. Therefore, besides generating public revenues, Taxes constitute tools for the establishment of inductive rules, as an instrument of Federal intervention in the Economic Domain, within the area reserved by the constitutional text. The Constitution placed this last function above the very fundamental rights of “Legality” and “Anteriority”, which allows assuming that such exceptions are also irrevocable, preventing their modification by Constitutional Amendments. The objective of this work is studying that relationship, using as a background the Financial Activities and the augmentation of the Federal competency for creating social contributions levied on corporate revenues. It is expected that this research will demonstrate if there is any incompatibility with those exceptions and limitations to fundamental rights of Taxpayers and the possibility of social contributions be levied – at least indirectly – on the same material tax basis, notwithstanding these types of taxes are subordinated to legal reserve in terms of determining its amount and its augmentation is only applied after ninety days after Congress approval